2019
DOI: 10.1002/masy.201800028
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible PCL/PLGA/Polypyrrole Composites for Regenerating Nerves

Abstract: In the field of regenerative medicine, many studies have focused on regenerating peripheral nerves because clinical problems and functional loss of organs are affecting an increasing number of people. Biocompatible polymers can be potentially used for producing biocompatible tubes in order to aid the regeneration of peripheral nerves. This study aims to prepare polymeric composites based on polycaprolactone (PCL), poly (lactic‐co‐glycolic acid) (PLGA), and polypyrrole fibers (PPy) capable of acting as a condui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 38 publications
1
19
0
1
Order By: Relevance
“…Owing to sustained-release properties, film-forming ability, favourable thermal stability, biocompatibility, and biodegradability, PLGA has been approved by the US FDA for biomedical applications [65,66]. PLGA-based materials are advantageous for tissue engineering purposes in that they have micropores on the surface that lead to high nutrient permeability and subsequently improvement of cell attachment and proliferation [67].…”
Section: Poly (Lactic-co-glycolic Acid) [Plga]mentioning
confidence: 99%
“…Owing to sustained-release properties, film-forming ability, favourable thermal stability, biocompatibility, and biodegradability, PLGA has been approved by the US FDA for biomedical applications [65,66]. PLGA-based materials are advantageous for tissue engineering purposes in that they have micropores on the surface that lead to high nutrient permeability and subsequently improvement of cell attachment and proliferation [67].…”
Section: Poly (Lactic-co-glycolic Acid) [Plga]mentioning
confidence: 99%
“…Polymeric NFs with electric conductive properties have been employed for engineering neuronal biointerfaces. As shown by Ferreira et al [ 197 ] the dispersion of polypyrrole (PPY) fibres (diameter in the 100–1000 nm range) within biodegradable PCL/PLGA polymeric matrix permitted to increase the electrical conductivity up to 0.1 S·cm −1 [ 197 ]. In another example, Nekouian et al [ 198 ] reported on the fabrication by electrospinning of PCL/PPY/MWCNTs fibrous structure for the electrical stimulation and differentiation of trabecular meshwork MSCs.…”
Section: 1d Polymeric Materialsmentioning
confidence: 99%
“…[5,6] To reduce the number of animals used, appropriate in vitro investigations can be used for screening prospective materials for estimations of toxic effects. [7,8] Cytotoxicity in vitro assay is the first test to evaluate the biocompatibility of any material used in biomedical devices. However, these tests have a great number of limitations and cannot mimic the biological environment.…”
Section: Introductionmentioning
confidence: 99%